Progress on Freedom of Religion or Belief?: An Analysis of European and North American Government and Parliamentary Initiatives - Toft, Monica Duffy (The review of faith & international affairs, 2018)
Threats to and violations of freedom of religion or belief (FoRB) have been increasing around the world for the last two decades. This has prompted governments to implement initiatives to promote FoRB and to condemn violations. Drawing on data and findings of the Commonwealth Initiative for Freedom of Religion or Belief (CIFoRB), this article presents an analysis of recent legislative, parliamentary, and executive branch initiatives in the U.S., Canada, U.K., and Norway to prioritize FoRB, for the lessons they afford on effective policy action. After an overview of these states' initiatives, this paper concludes with an assessment of their success.